2014
DOI: 10.1002/mpr.1440
|View full text |Cite
|
Sign up to set email alerts
|

The relation between procrastination and symptoms of attention-deficit hyperactivity disorder (ADHD) in undergraduate students

Abstract: Procrastination is defined as the tendency to delay activities that have to be completed before a deadline. It is often part of psychotherapies for adults with attention-deficit hyperactivity disorder (ADHD). However, procrastination is officially not acknowledged as an ADHD-related symptom. Therefore, little is known about the role of procrastination in ADHD. We investigated the relation between procrastination and ADHD-related symptoms of inattention, hyperactivity, and impulsivity in 54 students with varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…The results of the present study also revealed that the procrastination in adult patients with ADHD was not associated with hyperactivity and impulsivity. However, procrastination was associated with attention deficit as implied in previous research (Niermann & Scheres, 2014).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results of the present study also revealed that the procrastination in adult patients with ADHD was not associated with hyperactivity and impulsivity. However, procrastination was associated with attention deficit as implied in previous research (Niermann & Scheres, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…Based on the negative experiences related to procrastination, especially adolescents and adults with ADHD are prone to develop negative beliefs about the self (Steel, 2007). Procrastination was also associated with inattention, perfectionism, fear of failure, depression and low self-esteem (Niermann & Scheres 2014;Pychyl, Coplan, & Reid, 2002;Solomon & Rothblum, 1984). So, procrastination is often part of the psychotherapies for adults with ADHD who usually present low self-esteem and develop depression (Cook, Knight, Hume, & Qureshi, 2014;Daviss, 2008;Harpin, Mazzone, Raynaud, Kahle, & Hodgkins, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For these paired items, we included the item with the highest score in the sum score. The sum of these items led to a score for hyperactivity/impulsivity and a score for inattention, both ranging from 0 to 27, based on nine items each (see also Niermann and Scheres, ).…”
Section: Methodsmentioning
confidence: 99%
“…So far, only four studies have targeted procrastination in ADHD, and all of them reported an increased tendency of patients with ADHD to put off tasks and intended actions. Niermann and Scheres (2014) investigated the association of ADHD-related symptoms with procrastination in a nonclinical sample of students and found only inattention, but not hyperactivity and impulsivity, to be significantly related to procrastination. Ramsay (2016) described a case study of a college student with ADHD who procrastinates strongly.…”
Section: Introductionmentioning
confidence: 99%